Blockchain-Based Barangay Document Management System with OCR Data Extraction - Abubo, Katherine Dela Cruz; Ramos, Edlrin Dave Abarquez; Valencia, Faith Ansano; Sison, Ariel Antwaun Rolando; Abando, Diony; Blanco, Mark Christopher; Agustin, Vivien A. (IC-ITECHS, 2024)
This study introduces a Blockchain-Based Barangay Document Management System enhanced with Optical Character Recognition (OCR) to address the challenges of manual document handling in Philippine barangays. The system utilizes Blockchain to create an encrypted, tamper-proof ledger, ensuring data integrity and transparency by decentralizing document storage and preventing unauthorized alterations. AES-256 encryption and hashing algorithms protect transactions, while OCR technology digitizes physical records with 96% accuracy, reducing processing times by 50% and minimizing manual errors. The integration of Merkle Tree ensures each document’s uniqueness, and the system was evaluated against ISO 25010 standards, achieving high functionality, performance, and user satisfaction. This solution improves document security, reduces administrative workloads, and enhances service efficiency, fostering transparency and trust in local governance.